2017
DOI: 10.3389/fphar.2017.00146
|View full text |Cite
|
Sign up to set email alerts
|

Heme as a Target for Therapeutic Interventions

Abstract: Heme is a complex of iron and the tetrapyrrole protoporphyrin IX with essential functions in aerobic organisms. Heme is the prosthetic group of hemoproteins such as hemoglobin and myoglobin, which are crucial for reversible oxygen binding and transport. By contrast, high levels of free heme, which may occur in various pathophysiological conditions, are toxic via pro-oxidant, pro-inflammatory and cytotoxic effects. The toxicity of heme plays a major role for the pathogenesis of prototypical hemolytic disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 195 publications
3
108
1
4
Order By: Relevance
“…1A), which is consistent with previous reports that excess free heme is toxic via pro-oxidant, cytotoxic and proin ammatory effects [27]. In mammals, heme homeostasis can be maintained by hemopexin neutralization or HO-1 enzymatic hydrolysis of excess free heme, 30 µM heme can accumulate in mitochondria that synthesize heme [28], while in hemolytic diseases vascular endothelial cells may encounter up to 100 µM concentration of heme and open a selfprotective mechanism [25], suggesting that 20 µM heme is safe in dose, it was reported in Nature that heme at a dose of 50 mg/kg could speci cally degrade BACH1 in mice without affecting normal physiological functions [9]. Therefore, for the rst time, we attempted to use 20 µM heme to speci cally inhibit BACH1 expression in vascular endothelial cells, and observed that this effect could promote VEGF expression in vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…1A), which is consistent with previous reports that excess free heme is toxic via pro-oxidant, cytotoxic and proin ammatory effects [27]. In mammals, heme homeostasis can be maintained by hemopexin neutralization or HO-1 enzymatic hydrolysis of excess free heme, 30 µM heme can accumulate in mitochondria that synthesize heme [28], while in hemolytic diseases vascular endothelial cells may encounter up to 100 µM concentration of heme and open a selfprotective mechanism [25], suggesting that 20 µM heme is safe in dose, it was reported in Nature that heme at a dose of 50 mg/kg could speci cally degrade BACH1 in mice without affecting normal physiological functions [9]. Therefore, for the rst time, we attempted to use 20 µM heme to speci cally inhibit BACH1 expression in vascular endothelial cells, and observed that this effect could promote VEGF expression in vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 89%
“…Heme is a complex of iron and the tetrapyrrole protoporphyrin IX with essential functions in aerobic organisms, participate in biological oxygen transport, respiratory chain electron transfer, etc. It can be degraded to iron, carbon monoxide and biliverdin by HO-1, which has anti-in ammatory, antioxidant and anti-apoptotic effects [25]. It has been used in the treatment of porphyria hepatica, it is a safe and reliable drug, which can be orally and intravenously injected [26], more convenient and safer than intravitreal injection.…”
Section: Discussionmentioning
confidence: 99%
“…Surface plasmon resonance analysis indicated that the dissociation constant (K D ) and binding number for Bach1HBR-C WT with heme are 1.37 × 10 -5 M and 2.3, respectively. The dissociation constant represents a relatively low affinity, and other heme-binding proteins exhibit K D values from 1 × 10 -6 M (α1-microglobulin) to 1 × 10 -14 M (hemopexin) (Immenschuh et al 2017). In our previous report, we found the K D value for Bach2 with heme to be 1.67 × 10 -7 M (Suenaga et al 2016).…”
Section: Heme Binds To the Cp Motifmentioning
confidence: 88%
“…Hemopexin is a scavenger protein of haemoglobin and a predominant heme binding protein, which contributes to heme homeostasis (Smith and McCulloh, 2015;Immenschuh et al, 2017). Hemopexin also associates with high density lipoproteins (HDL), influencing their inflammatory properties (Mehta and Reddy, 2015).…”
Section: Discussionmentioning
confidence: 99%